Digital Storytelling in Speaking Class of Vocational High School - Muttaqin, Bindu Risyad (RETAIN : Journal of Research in English Language Teaching, 2023)
The purpose of this study is that researcher want to find out about how the Digital Storytelling technique can be implemented in high school, vocational school and how the technique can help learners to improve their English speaking. Learners can use Digital Storytelling to enhance their speaking in front of the class and overcome their nervousness. In the same vein, research method used as a minor the method used research design to full fill this research and the subject of participants are the learners of vocational high school student at 10th grade. The speaking result which will be in form of speaking rubric will be conducted to collect the data. The Digital Storytelling as bridge for learners to enlarged their capability to in speaking skill. Since Digital Storytelling is used in narrative, learners get improved speaking, new vocabulary and group collaboration. As a result, it can help them to improve their ability to learn English.